TRUST IN WORD-OF-MOUTH OF FRIENDS, STRANGERS OR BRAND AMBASSADOR IN PRODUCT PURCHASE DECISIONS: A QUALITATIVE ANANLYSIS OF TRUST ISSUES - KOMAL, MISHTY (2013)
This paper is an exploratory study of the influence of word-of-mouth on the consumer's intentions to buy. The word-of-mouth being referred to and explained in this study is face-to-face conversations between consumers and their friends and online exchange of product related information through online consumer reviews. This study covers the aspects of traditional word-of-mouth and electronic word-of-mouth and their comparison in the degree of their influence on the consumers. This study interprets their strategic behaviour when they are being framed in situations where they are questioned about the trust issues arising to trust strong-ties, weak-ties and paid opinion leaders such as brand ambassadors. The findings show that the millennial generation is sceptical in trusting firm initiated sources of information and rely on the recommendations of their peers. The findings also show that they consider strangers or weak-ties as more credible sources of information than the brand ambassadors. The study also highlights the importance of social network sites such as Facebook in joining the influential marketing culture and how the marketers trigger word-of-mouth using these social platforms to their advantage. This takes study takes strangers trustworthiness to the next level making them a new emergent and strong influential force in the buyer's decision making. This research reveals the opinions and views of the millennial consumers towards the celebrity brand endorsers and also brand endorsers in general. The consumers are questioned if they would trust strong-ties if they were paid agents of the company to promote the product and makes an effort to interpret their dilemmas and the strategies they acquire to get out of it. Several implications to the companies and the marketing managers are discussed in the study. The major implication being to let the positive word-of-mouth of a product generate in an organic manner without exploiting the consumers vulnerability and helplessness.